Tinjauan Teoritis Peraturan Pencegahan Value Added Tax Fraud Dan Value Added Tax Evasion - Setiadi Alim Lim; Lilik Indrawati (Universitas Katolik Darma Cendika, 2020)
Overall the existing taxation regulations in Indonesia are good enough to prevent the possibility of Value Added Tax Fraud and Value Added Tax Evasion. For each violation committed will be subject to sanctions. Unintentional violations will be subject to administrative sanctions, while intentional violations of Value Added Tax Fraud and Value Added Tax Evasion in addition to administrative sanctions will also be subject to criminal sanctions to provide a deterrent effect. The use of communication and information technology in the tax administration system in the form of e-Invoice and e-SPT for Value Added Tax is very helpful in preventing Value Added Tax Fraud and Value Added Tax Evasion. However, it is necessary to improve policies and regulations so that Value Added Tax Fraud and Value Added Tax Evasion can be minimized even more.